Design of intelligent fault diagnosis system based on naval vessel's cooling system of diesel engine - Zhou Xianglong; Gao Feng; Zhao Jingbo (2010 8th World Congress on Intelligent Control and Automation, 2010)
Aimed at the defect of low veracity and inefficient tradition fault diagnosis, an intelligent fault diagnosis system of a naval vessel's cooling system for diesel engine is designed. Based on improved Back Propagation neural network algorithm and realized by Visual Basic loading Dynamic Link Library which by C++. Application results show that it has the more strong ability of self learning and self adaptation.